Austronesian Paths and Journeys - Fox, James J. (Comparative Austronesian Series, 2021)
This is the eighth volume in the Comparative Austronesian series. The papers in this volume examine metaphors of path and journey among specific Austronesian societies located on islands from Taiwan to Timor and from Madagascar to Micronesia. These diverse local expressions define common cultural conceptions found throughout the Austronesian-speaking world.